2014
DOI: 10.1089/thy.2013.0232
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Thyroid Cancer: A Clinical Update

Abstract: Given the rising prevalence of TC and the development of obesity as an epidemic, it is important to clarify its connection with TC as well as the mediating pathways. However, unless this association is confirmed and causation proven, screening for TC in overweight and obese subjects-a rapidly increasing body of the general population-does not seem justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 52 publications
3
105
0
3
Order By: Relevance
“…The average age of these patients was 56.7 years at diagnosis, higher than the average age of 45.4 years among those staged as pT1N0/N1, pT2N0/N1, pT3N0. Associations with older age (1,11), multifocality (7,10), and the presence of lymph node metastases (7,12) with advanced stages and prognosis were reported in differentiated thyroid carcinoma. Of the 68 patients who had differentiated carcinoma and developed distant metastases (9.2%), 46 were age 50 years or older at the diagnosis of their primary tumors, three of whom were less than 20 years old (mean 55.2 years).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The average age of these patients was 56.7 years at diagnosis, higher than the average age of 45.4 years among those staged as pT1N0/N1, pT2N0/N1, pT3N0. Associations with older age (1,11), multifocality (7,10), and the presence of lymph node metastases (7,12) with advanced stages and prognosis were reported in differentiated thyroid carcinoma. Of the 68 patients who had differentiated carcinoma and developed distant metastases (9.2%), 46 were age 50 years or older at the diagnosis of their primary tumors, three of whom were less than 20 years old (mean 55.2 years).…”
Section: Discussionmentioning
confidence: 97%
“…Many carcinomas were characterized as incidentalomas, following the current trend (7,8). However, the outcome was not always favorable in these patients and included associated deaths, as shown in with papillary carcinoma pT1bN0 at ages 61 and 65 years died, one due to distant metastasis diagnosed 23 months after the initial diagnosis and the other due to the local recurrence diagnosed 84 months after the thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…(Engeland et al 2006). As a matter of fact, several studies have reported these differences between obese men and women and their risk of thyroid cancer, allowing speculation regarding hormone effects or the insufficiency of male cases analyzed, as thyroid cancer incidence is higher in women (Pappa & Alevizaki 2013). Other subsequent studies showed associations of weight, BMI, body surface area, and/or overweight/obesity and DTCs, demonstrating that these parameters elevated the risk of developing these cancers (Brindel et al 2009, Mijovic et al 2009, Clero et al 2010, Leitzmann et al 2010.…”
Section: Association Between Overweight and Thyroid Cancer: Observatimentioning
confidence: 98%
“…In 1987, during the decade when the first obesity boom was reported, Albanes (1987) reviewed a series of studies concerning the relationship between overweight and different cancer types and observed that subjects with high relative body weight or high caloric intake were at a higher risk of developing breast, colon, rectum, prostate, endometrium, kidney, cervix, ovary, thyroid, and gallbladder cancers. But in the case of thyroid cancers, it was only after the year 2000 that larger studies started to appear with the first solid evidence (Pappa & Alevizaki 2013).…”
Section: Association Between Overweight and Thyroid Cancer: Observatimentioning
confidence: 99%
“…In addition, an imbalance between estrogens (E2) and androgens, due to the action of aromatase in the adipose tissue, could contribute to thyroid carcinogenesis in obese patients, being responsible for different actions according to gender and age (152). In thyroid cancer cells, the biological effects of E2 are mediated by estrogen receptors a (ERa (ESR1)) in an ERK1/2-related pathway (153).…”
Section: Thyroid Cancer In Obese Patientsmentioning
confidence: 99%